In Her Shoes : Modemuseum Hasselt. - Ramaekers, Kenneth; Dehullu, Joanie (Hasselt : Modemuseum Hasselt, 2009)
Bally ; Perugia, André ; Ferragamo, Salvatore ; Izegem industrie ; Jourdan, Charles ; Levine, Beth ; Levine, Herbert ; Vivier, Roger ; Pfister, Andrea ; Frizon, Maud ; Jansen, Jan ; Kumagai, Tokio ; de Havilland, Terry ; Feldman, Beverly ; Rossi, Sergio ; Cox, Patrick ; Choo, Jimmy ; Blahnik, Manolo ; Louboutin, Christian ; Proost, Els ; Verbeek, Ellen ; Verlinden, Nathalie ; Hermans, Linde ; Volleberg, Renate ; Van den Berg, René ; ten Bhömer, Marloes ; Koolhaas, Rem D ; Rietjens, Helena ; Fielden, Alexander ; Peterson, Jelske ; Huskens, Gwendolyn ; Tcherevkoff, Michel ; Van Sande, Guy ; Fielden, Christian
In Her Shoes, Modemuseum Hasselt, Hasselt, 30 mei - 8 november 2009
boek